Criminal Action Without Proven in Money Laundering in Indonesia - Ilato, Fadel; Majid, Abdul; Noerdajasakti, Setiawan (Jambura Law Review, 2021)
Money laundering is a follow-up crime, an underlying crime from a predicate crime, so that the existence of money laundering cannot be separated from the original crime. How can money laundering occur without proving the original crime? Therefore, the aim of this study is to analyze the legal implications of predicate offenses without substantiation in money laundering in Indonesia. This research is juridical-normative research, which uses a statutory approach and a case approach. The results of this study indicate that there are legal implications for predicate offenses without proof in money laundering in Indonesia. Starting from breaking through the presumption of innocence and inconsistencies in legal norms in the TPPU Law. So, it is necessary to change the construction of norms contained in article 69 related to proving predicate crimes in TPPU.